Efficacy Evaluation of Ciprofloxacin-Loaded Poly (Trimethylene Carbonate) Implants in the Treatment of Chronic Osteomyelitis - Liu, Yixiu; Liang, A.; Li, Xu; Ma, Zhihe; Zhang, Dan (Frontiers in Bioengineering and Biotechnology, 2022)
Ciprofloxacin-loaded poly(trimethylene carbonate) (PTMC) implants were prepared for treating chronic osteomyelitis, and the antibacterial effects in vitro or in vivo were both evaluated. The in vitro results showed that the Ciprofloxacin-loaded PTMC implants could sustain release ciprofloxacin at a release amount of about 90 μg/d for 28 days and possessed excellent antibacterial effect, as evidenced by the smaller size of the antibacterial ring of 32.6 ± 0.64 mm and the biofilm inhibition of 60% after 28 days of release. The in vivo results showed that after 28 days of treatment, the body weight and the white blood cell counts of chronic-osteomyelitis-model rats in the treatment group reached 381.6 ± 16.8 g and (7.86±0.91) ×109/L, respectively, returning to normal rapidly compared with the control group and blank group, indicating the remarkable antibacterial effect of the Ciprofloxacin-loaded PTMC implants. X-ray images and HE staining results also confirmed that most of the proximal and middle parts of the tibia returned to typical structures and new and trabecular bone had been formed for the rats in the treatment group, and no inflammatory cells were found as compared to the control and blank groups, after 28 days of treatment. The significant lower number of colonies of (9.92 ± 1.56)×10 CFU/g in the treatment group also suggests that the Ciprofloxacin-loaded PTMC implants achieve a practical antibacterial effect through a local application.